Association in the Perspective of Hadith: Analyzing Ma'ani al-Hadith Using John Locke's Empiricism Theory in Education - Ichwayud, Budi; Rifai, Surur; syafik R, moh; Maâ€™rifatul A, Zulfa; Fika Mubaddillah, Ari (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
Association is fundamental to human life, as highlighted in the Qur'an Al-Mumtahanah verses 8-9. Marzuki Wahid interprets this verse to refer to kafir harbi, indicating that Muslims may socialize and engage in mu'amalah with non-Muslim communities, except those who are hostile (kafir harbi). Other opinions included prohibiting associations with hypocrites, major sinners, and immoral individuals. The hadith a man follows the religion of his friendâ€ emphasizes the importance of considering one's associations. This study used qualitative research methods and a library research approach to examine hadiths. John Locke's empiricism theory of education is applied to analyze the hadith's implications on social relations and education. The findings are that the hadith does not prohibit social relations or mu'amalah with non-Muslims but advises caution in choosing close friends to protect oneâ€™s faith. From the perspective of Locke's empirical theory of education, this hadith is relevant and does not present contradictions. This study suggests that Muslims are encouraged to choose friends wisely to maintain their religious integrity while promoting moderate and inclusive social behavior in diverse religious contexts. The alignment of hadith with Locke's empiricism theory underscores the significance of the environmental influence on personal development and education. This hadith offers valuable guidance on social interactions, emphasizing the importance of selecting friends who positively influence faith and character. Through the lens of empiricism theory, hadith supports the idea that one's environment and associations play a crucial role in shaping behavior and personality, encouraging moderate and inclusive social relations in diverse communities